Academic–Practitioner Relationships: What NTL Started and What Management Scholarship Keeps Developing. (December 2014) - Bartunek, Jean M.
At the time the Journal of Applied Behavioral Science ( JABS ) began publishing 50 years ago, much social science scholarship took the form of basic research, with relatively little attention to practice. Thanks to the impetus of Kurt Lewin and the National Training Laboratories, the focus of JABS was much more on relationships between theory and practice than was most other scholarship; the expectation was that JABS would focus on scholarly knowledge that would also inform practice. Over the course of the past half century, however, there has taken place some separation of academic scholarship and practice with regard to organization development. During this same time period there have been several developments in other areas of management inquiry in which academic–practitioner links have been fostered. In this article, I will explore the patterns that have occurred, indicate some questions they raise for JABS going forward, and suggest some possible implications for publishing practice in JABS . These implications include both communication issues with regard to publishing and substantive issues regarding what "counts" as organization development.